Hitler's true believers : how ordinary people became Nazis - Gellately, Robert (Oxford University Press, 2020)
Zusammenfassung: Nazi ideology drove Hitler's quest for power in 1933, colored everything in the Third Reich, and culminated in the Second World War and the Holocaust. In this book, Gellately addresses often-debated questions about how Führer discovered the ideology and why millions adopted aspects of National Socialism without having laid eyes on the "leader" or reading his work.